Pengaruh Brand Image, Electronic Word Of Mouth dan Harga terhadap Purchase Intention pada Produk Mixue di Kecamatan Sidoarjo - Vernanda Suyono Putri; Rizky Eka Febriansah; Dewi Komala Sari (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Mixue is a franchise business originating from Tiongkok that offers several ice cream variants. This research aims to determine the influence of brand image, electronic word of mouth and price on purchase intention for mixue products in Sidoarjo District. This research uses a quantitative approach. The method used was accidental sampling with a sample size of 100 respondents of mixue consumers in Sidoarjo District. The data analysis technique used was multiple linier regression analysis using the imb spss 25 program. Based on the research results, it was found that the brand image variable has a positive but not significant effect on purchase intention, electronic word of mouth has a positive and significant effect on purchase intention and price has a positive and significant effect on purchase intention.